Bakuchiol and Ethyl (Linoleate/Oleate) Synergistically Modulate Endocannabinoid Tone in Keratinocytes and Repress Inflammatory Pathway mRNAs - William R. Swindell; Krzysztof Bojanowski; Parvesh Singh; Manpreet Randhawa; Ratan K. Chaudhuri (Elsevier, 2023)
The endocannabinoid (eCB) system plays an active role in epidermal homeostasis. Phytocannabinoids such as cannabidiol modulate this system but also act through eCB-independent mechanisms. This study evaluated the effects of cannabidiol, bakuchiol (BAK), and ethyl (linoleate/oleate) (ELN) in keratinocytes and reconstituted human epidermis. Molecular docking simulations showed that each compound binds the active site of the eCB carrier FABP5. However, BAK and ethyl linoleate bound this site with the highest affinity when combined 1:1 (w/w), and in vitro assays showed that BAK + ELN most effectively inhibited FABP5 and fatty acid amide hydrolase. In TNF-stimulated keratinocytes, BAK + ELN reversed TNF-induced expression shifts and uniquely downregulated type I IFN genes and PTGS2 (COX2). BAK + ELN also repressed expression of genes linked to keratinocyte differentiation but upregulated those associated with proliferation. Finally, BAK + ELN inhibited cortisol secretion in reconstituted human epidermis skin (not observed with cannabidiol). These results support a model in which BAK and ELN synergistically interact to inhibit eCB degradation, favoring eCB mobilization and inhibition of downstream inflammatory mediators (e.g., TNF, COX-2, type I IFN). A topical combination of these ingredients may thus enhance cutaneous eCB tone or potentiate other modulators, suggesting novel ways to modulate the eCB system for innovative skincare product development.